Stereological Estimation of Mean Nuclear Volume as a Prognostic Factor in Canine Mast Cell Tumors - Casanova, M (2019)
STEREOLOGICAL ESTIMATION OF MEAN NUCLEAR VOLUME AS A PROGNOSTIC FACTOR IN CANINE MAST CELL TUMOURS M. Casanova*, S. Branco*, I. Veiga† and P. Faísca‡ *Departamento de Medicina Veterinária, Universidade de Évora, Évora, Portugal, †Institut für Tierpathologie, Vetsuisse Bern, Bern, Switzerland and ‡Histopathology Unit, Instituto Gulbenkian de Ciência, Oeiras, Portugal Introduction: Cutaneous Mast Cell Tumour (MCT)’s Patnaik and Kiupel grading schemes rely on qualitative and semi-quantitative features susceptible to inter-observer variability. Stereological estimation of volume-weighted mean nuclear volume (MNV) provides information about both size and variability of nuclear size, which has been proven to have a prognostic value in other solid tumours. The objective was to compare MNV with MCT grade and biological behaviour. Materials and Methods: 56 MCTs were graded according to Patnaik and Kiupel by consensus of three experienced pathologists. Clinical history of dogs treated with surgical excision alone was collected with a minimum follow-up period of one year (n=31). MNV was estimated using the point-intercept method on vertical sections in 10 microscopic fields, with an approximately constant distance proportional to overall sectional area. Animals were divided according to outcome: (group 1) no recurrence; (group 2) local recurrence, lymph node or distant metastasis. Statistical analyses of results were performed by the Mann-Whitney U Test and Receiver Operating Characteristics (ROC) curve. Results: MNV of low-grade (n=35) and high-grade (n=20) was 139.6 (±35.2) μm³ and 222.9 (±80.4) μm³, respectively. MNV of grade II (n=39) and grade III (n=16) was 145.6 (±38.6) μm³ and 229.0 (±88.6) μm³, respectively (P<.0001, Mann-Whitney U test). An optimal cut-off value of MNV>169 μm³ (81% sensibility and 78% specificity) was shown to differentiate MTCs with a more aggressive behaviour (group 2). Conclusions: The present study suggests that estimation of MNV on routine histological sections may objectively improve the detection of more aggressive MCTs. Acknowledgements: The authors thank Inês Carvalho at DNATech, Portugal and Joana Rodrigues at the Histopathology Unit (IGC), Portugal for technical contributions.